RAGAM HIAS SASAMBO BERTEMA SIRKUIT MANDALIKA SEBAGAI MEDIA PEMBELAJARAN SENI RUPA BAGI CALON GURU SEKOLAH DASAR - -, Nurul kemala Dewi; Safruddin; Siti Istiningsih; Raodatul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to create Sasambo ornamental designs themed around the Mandalika Circuit as learning media for visual arts education in pre-service elementary teacher training. The research adopts an artistic creation research approach, employing three sequential stages: exploration, design, and realisation. Data were generated through visual observation, document analysis, and process documentation. The design process was guided by fundamental principles of visual arts, including proportion, rhythm, harmony, balance, emphasis, and unity. The creative outcomes consist of four ornamental works: The Mandalika Subahnale, The Mandalika Kemang Aruna, The Mandalika Piyo Merak’s, and The Mandalika Sasak’ Puppet. These works represent a reinterpretation of traditional Sasambo ornamentation—rooted in Sasak, Samawa, and Mbojo visual traditions—through the integration of the Mandalika Circuit as a contemporary visual icon. The findings demonstrate that art creation grounded in local cultural heritage and contemporary visual contexts has the potential to function as a reflective pedagogical medium that fosters visual literacy, creativity, and cultural awareness among pre-service elementary school teachers.